Corticospinal Modulations during Bimanual Movement with Different Relative Phases - Nomura, Yoshifumi (Front Hum Neurosci, 2016)
The purpose of this study was to investigate corticospinal modulation of bimanual (BM) movement with different relative phases (RPs). The participants rhythmically abducted and adducted the right index finger (unimanual (UM) movement) or both index fingers (BM movement) with a cyclic duration of 1 s. The RP of BM movement, defined as the time difference between one hand movement and the other hand movement, was 0°, 90°, or 180°. Motor evoked potentials (MEPs) in the right flexor dorsal interosseous muscle elicited by transcranial magnetic stimulation (TMS) were obtained during UM or BM movement. Corticospinal excitability in the first dorsal interosseous muscle during BM movement with 90° RP was higher than that during UM movement or BM movement with 0° or 180° RP. The correlation between muscle activity level and corticospinal excitability during BM movement with 90° RP was smaller than that during UM movement or BM movement with 0° or 180° RP. The higher corticospinal excitability during BM movement with 90° RP may be caused by the greater effort expended to execute a difficult task, the involvement of interhemispheric interaction, a motor binding process, or task acquisition. The lower dependency of corticospinal excitability on the muscle activity level during BM movement with 90° RP may reflect the minor corticospinal contribution to BM movement with an RP that is not in the attractor state.